Women in Freedom Fights: state of research and methodological insights - Jurkutė, Mingailė; Kripienė, Enrika (Genocidas ir rezistencija, 2024)
The topic of the article is women in the Lithuanian guerrilla war. The authors review the development of the topic in Western historiography and the changing theoretical and methodological approaches, and then discuss the case of the Lithuanian guerilla war. Firstly, the image of female partisan war participants (participation in a broad sense, from combatants to assisting the resistance in different ways) is reviewed in a broad time perspective, from the period of partisan struggle to the Second Republic of Lithuania. Secondly, Lithuanian historiography is analyzed.The research reveals that, just like in the Western historiography, in the early period, while the partisan struggle was still ongoing, the first collective images appeared as uncritical, little reflected, idealized, and propagandized. Under the conditions of the Soviet regime, Lithuanian historiography did not develop, so after independence was restored, the same images – now supported by several of the earliest narrative sources (Juozas Lukša’s memoirs, Lionginas Baliukevičius’s diary) – crossed over into historiography, and are still widespread in the popular historical consciousness to this day. Propaganda about the Lithuanian guerilla war of the Soviet period did not offer any specific images of the female participants. In the last decade new multicentric efforts to approach the research of women in the Lithuanian armed resistance (in terms of theory and methodology), as well as in social history in general, are observed.Finally, the authors formulate possible guidelines for further research: to analyze the quantitative and qualitative data collected so far, to present a detailed statistical analysis of women in the partisan war; to study women within the context of social history, combining research on women’s participation in guerrilla warfare with the social development of the society; to study the history of war memory simultaneously with the research of guerilla war; to use the interview method more extensively, since examples in Western research have revealed that conventional written sources do not capture the specific experiences of women.
Keywords: Second World War; guerrilla warfare; postwar; freedom fights; women; women's history; gender studies